The influence of refurbishment project to economy & life quality from public perception. Case study: Central Market area, Kuala Lumpur / Noor Azizan Ab Aziz - Ab Aziz, Noor Azizan (2006)
Malaysia is one of the privileged countries that have many historical buildings which are of immense of architectural and historical values. It is believed that there are more than 37, 000 historical buildings built between 1800 and 1948 throughout the country which are worthy for preservation and conservation. Conservation by definition is guardianship providing for maintenance, preservation or protection of what presently exists, from being destroyed or changed in an inappropriate manner. In the past few years, many historic buildings in our country have been preserved and conserved while others have been refurbished to meet current need of function for such building example bank, restaurant, information centre or a printing office. With regard to this, I therefore decided to identify the influence of refurbished project to economy and life quality in Wilayah Persekutuan Kuala Lumpur with case study at Central Market area which was built in 1936 and addressed nearly at Jalan Hang Kasturi, 50050, Kuala Lumpur. The main content of this dissertation is to identify the contribution of Refurbishment Projects to the Kuala Lumpur's economy and life quality. Discussion of the dissertation will be the general view of refurbishment including the trend in Malaysia and then observation of Kuala Lumpur life.